SLC17A6/7/8 Vesicular Glutamate Transporter Homologs in Nematodes - Serrano-Saiz, Esther (Genetics, 2020)
Members of the superfamily of solute carrier (SLC) transmembrane proteins transport diverse substrates across distinct cellular membranes. Three SLC protein families transport distinct neurotransmitters into synaptic vesicles to enable synaptic transmission in the nervous system. Among them is the SLC17A6/7/8 family of vesicular glutamate transporters, which endows specific neuronal cell types with the ability to use glutamate as a neurotransmitter. The genome of the nematode Caenorhabditis elegans encodes three SLC17A6/7/8 family members, one of which, eat-4/VGLUT, has been shown to be involved in glutamatergic neurotransmission. Here, we describe our analysis of the two remaining, previously uncharacterized SLC17A6/7/8 family members, vglu-2 and vglu-3. These two genes directly neighbor one another and are the result of a recent gene duplication event in C. elegans, but not in other Caenorhabditis species. Compared to EAT-4, the VGLU-2 and VGLU-3 protein sequences display a more distant similarity to canonical, vertebrate VGLUT proteins. We tagged both genomic loci with gfp and detected no expression of vglu-3 at any stage of development in any cell type of both C. elegans sexes. In contrast, vglu-2::gfp is dynamically expressed in a restricted set of distinct cell types. Within the nervous system, vglu-2::gfp is exclusively expressed in a single interneuron class, AIA, where it localizes to vesicular structures in the soma, but not along the axon, suggesting that VGLU-2 may not be involved in synaptic transport of glutamate. Nevertheless, vglu-2 mutants are partly defective in the function of the AIA neuron in olfactory behavior. Outside the nervous system, VGLU-2 is expressed in collagen secreting skin cells where VGLU-2 most prominently localizes to early endosomes, and to a lesser degree to apical clathrin-coated pits, the trans-Golgi network, and late endosomes. On early endosomes, VGLU-2 colocalizes most strongly with the recycling promoting factor SNX-1, a retromer component. Loss of vglu-2 affects the permeability of the collagen-containing cuticle of the worm, and based on the function of a vertebrate VGLUT1 protein in osteoclasts, we speculate that vglu-2 may have a role in collagen trafficking in the skin. We conclude that C. elegans SLC17A6/7/8 family members have diverse functions within and outside the nervous system.